What we can and what we can't say about employment growth in specialised cities - Oliver Farhauer; Alexandra Kröll (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2010)
There is an ongoing debate on whether certain sector structures enhance regional employment growth. Often, regional policies promote clusters and, hence, regional specialisation. It is commonly believed that clusters boost regional economic performance. However, in the present manuscript a simple model is introduced which suggests the reverse is true regarding employment growth. It is argued that specialised regions are prone to be affected stronger by sector-specific demand shocks than diversified ones and, therefore, show higher variances in employment growth rates. A test on the equality of variances in employment growth rates across two groups of specialised and diversified cities is conducted. It shows that, in Germany, variances are higher in the group of specialised cities. Thus, regional specialisation is more insecure than diversification with regard to stable employment growth rates.
Keywords: O18; R11; J21; 330